Report of the Work of the National Joint Committee for Spanish Relief, The British Committee for Refugees from Spain and The Basque Children's Committee (1939)
1939 038-0069-010 Cheshire Committees have undertaken all responsibility for large groups of refugees during the last six months. Many of these Spaniards in England are exceptionally well suited for employment at the present time, either in the A.R.P. services by reason of their previous experience of war conditions, or in some technical trade. These men have offered their services to the British Government and it is the hope of the Committee that England may benefit by their experience and service. There are also in England more than 100 Spanish senoritas who originally came to this country with the Basque children, as teachers and domestic helpers in the Basque Children's Homes. Many of these will be unable to return to Spain. The Home Office is prepared to allow them to accept domestic work and offers of employment of this nature will be gladly received at the National Joint Committee's Office at 30 Eccleston Street. THE BASQUE CHILDREN In co-operation with the Basque Children's Committee the National Joint Committee has been responsible for the maintenance in this country of 4,000 Basque children who were brought here at the earnest request of their parents after the destruction of Guernica. More than 3,000 of these children have now been repatriated, and a further 300 will leave as soon as transport can be arranged for them under present war conditions. The parents of the remainder are refugees from Spain, and to return their children to Bilbao might therefore mean a life-long separation of families. These six or seven hundred who will be left in England are therefore entirely dependent upon us for their existence, and the obligation upon us to maintain them is stronger now than ever, since so many of their parents are now on French soil. To keep these children for two and a half years in security here has been no light task. We estimate that more than £165,000 has been raised for this purpose by voluntary contributions. In accordance with the promise given when the children were first brought over, they have never been a charge upon public funds. Those who must still remain in England have the strongest possible claim upon our sympathy. For the second time in their lives they are faced with the menace of modern warfare. We are doing all that we can to ensure their safety, but funds, clothes, and above all offers of private hospitality are urgently required until it is possible to restore them to the parents from whom they have so long been separated. 6 292/946/38/69(X)